The relevance of bibliometric analysis to discover the area's research efforts: Root exploit evolution - Che Akmal, Che Yahaya; Ahmad, Firdaus; Ernawan, Ferda; Wan Isni Sofiah, Wan Din (Politeknik Negeri Padang, 2022)
Malware steals, encrypts, and damages data of the targeted machines for private, money, or fame purposes. The types of malwares are root exploit, cryptojacking, Trojan, worms, viruses, spyware, ransomware, and adware. Among these types, root exploit is one of the most destructive malware types since it disguises and obscures all types of malwares and provides a mechanism for other malware to carry out malicious acts invisibly. To review the progress of root exploitation efforts globally, there is a need to inspect all publications that involve root exploitation. Among all malware reviews previously, to date, there is still no trace of any bibliometric analysis that demonstrates the research impacts of root exploit and trends in bibliometric analysis. Hence, this paper adopts bibliometric analysis specifically on root exploit studies which evaluate: (1) Wordcloud; (2) WordTreeMap; (3) Three fields plot; (4) Thematic evolution; (5) Thematic maps; (6) Correspondence analysis (CA); (7) Dendrogram; and (8) Multiple correspondence analysis (MCA). To conclude, our bibliometric discovers that; 1) Linux and Android become the main interest in root exploit studies. 2) Types of root exploit in the virtualization layer and studies to detect this area are increasing. 3) USA and China have become the leaders in root exploitation research. 4) Research studies are more towards memory forensics to detect root exploit, which is more promising. 5) Instead of researching new methods of root exploit in compromising victims, root exploits researchers were more focused on detecting root exploits.